Romans : The NIV Application Commentary : Biblical Text ... to Contemporary Life - Moo, Douglas J. (Grand Rapids, Mich. : ZondervanPublishingHouse, 2000)
Our culture does not encourage thoughtful reflection on truth. Yet living the gospel in a postmodern culture demands that Christians understand and internalize the truth about God and his plan for the world. Paul's letter to the Romans remains one of the most important expressions of Christian truth ever written. Its message forces us to evaluate who we are, who God is, and what our place in this world ought to be. Going beyond the usual commentary, this volume brings the meaning of Paul's great letter into the twenty-first century. Douglas Moo comments on the text and then explores issues in Paul's culture and in ours that help us understand the ultimate meaning of each paragraph. A final section suggests ways in which the eternal theology of Romans can be understood and lived out in our modern culture.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; Romans - Commentary; NIV Application Commentary; Commentaries